Analisis Kualitas Pelayanan Perpustakaan Menggunakan Metode Kano - Kasmawati Kasmawati; Sofiyanurriyanti Sofiyanurriyanti (Universitas Teuku Umar, 2023)
The West Aceh Regency Library and Archives Service is an agency engaged in carrying out general government tasks, building libraries, and providing services openly to its users regardless of age, education, and social status factors in society. However, there are still some problems that make visitors unsatisfied, including incomplete and non-specific book collection facilities, lack of the latest published books, placement of books on shelves that do not match the location, and inadequate facilities in the reading room. This study aims to determine and categorize the attributes that are considered important from the desire of visitors to know the quality of services provided by the West Aceh District Library and Archives Service using the canoe method. The Kano method is one of the simple methods that can improve products and services to customers. This method is a model that classifies attributes and is analyzed based on customer perceptions, and the effect on customer satisfaction. The results of calculating the average value of service quality in all dimensions of the canoe method show that visitors are not satisfied enough and there are still deficiencies in service quality at the West Aceh Regency Library and Archives Service. Of the 22 attributes, some attributes need to be improved, namely one-dimensional category attributes 5,8,9,11,14,16, and 19, indifferent category attributes 10,13,15,17,18,20,21 and 22, attributes The ones that are maintained are the attractive 12 categories and the attributes that need to be improved are the must-be categories 1,2,3,4,6, and 7 which illustrate that the more an attribute does not function properly, the visitor satisfaction will decrease.